Effect of Sugar Beet Molasses and Compost from Brewery Sludge on Celery (Apium graveolens var. rapaceum) Yield and Nutrient Uptake - Boris Adamović; Đorđe Vojnović; Ivana Maksimović; Marina Putnik Delić; Dragan Kovačević; Ranko Čabilovski; Milorad Živanov; Maja Ignjatov; Janko Červenski; Dragana Latković (Horticulturae)
The rising cost of mineral fertilizers and the decreasing availability of manure in vegetable farming highlight the need for alternative fertilization strategies. To examine the possibility of applying byproducts from the food processing industry, sugar beet molasses, and compost from brewery sewage sludge in celery production, the field experiment was conducted over two years, using a randomized complete block design with three replications. The examined variants were T0—control (without fertilizer); T1—mineral fertilizer; T2—cattle manure; T3—sheep manure; T4—poultry manure; T5—supercompost; and T6—molasses. In the first year, there was no significant difference between T1 and T5 in thickened root yield, while these two variants achieved significantly higher yield compared with other variants. In both years, the highest leaf yield was achieved with T1, while no significant difference was found between T5, T6, and conventional organic fertilizers of animal origin. The highest amount of N was absorbed by roots in T1 (42.0 kg/ha and 51.2 kg/ha, respectively), while the lowest amount was absorbed in T0 (25.5 kg/ha and 26.7 kg/ha, respectively). A significantly higher amount of P2O5 was absorbed by roots in all organic fertilizer variants compared to T0 and T1. In both years, of all the nutrients, K2O was the most absorbed nutrient by the celery root, while CaO was absorbed in greater quantities than N. Based on two years of research, it can be concluded that compost from brewery sludge and sugar beet molasses can be used as an alternative source of nutrients for plants.